(untitled) (Analysis in Theory and Applications, 2017)
In this paper, the authors introduce certain Herz type Hardy spaces with variable exponents and establish the characterizations of these spaces in terms of atomic and molecular decompositions. Using these decompositions, the authors obtain the boundedness of some singular integral operators on the Herz type Hardy spaces with variable exponents.